Visualisation of dCas9 target search in vivo using an open-microscopy framework - Koen J. A. Martens (Nature Portfolio, 2019)
Single-particle tracking PALM (sptPALM) provides quantitative information in vivo if the protein of interest remains in a single diffusional state during track acquisition. Here the authors develop a custom-built sptPALM microscope and a Monte-Carlo based diffusion distribution analysis to study dynamic DNA-dCas9 interactions in live bacteria.